PENINGKATAN AKTIVITAS DAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS V SD NEGERI 096117 BARINGIN RAYA TAHUN AJARAN 2022/2023 - Melisa Nur Asima Sidabutar (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to improve learning achievement, student activity in learning Indonesian with Media Pictures. The research subjects were fifth grade students at SDN 096117 Baringin Raya with a total of 25 students, consisting of 12 male students and 13 female students. The variables/factors investigated in this study were student achievement and student activity in learning. The method used in this study is the Picture and Picture learning model with picture media. From the results of this study it was found that the average learning outcomes obtained in learning Indonesian with media images were cycle 1 59, cycle II 66 and cycle III 74. Meanwhile, the percentage of classical completeness obtained in each cycle was cycle 1 52%, cycle II 78 % and 86% cycle III. While the average results of student activity in cycle 1 2.3 with good criteria, cycle II 2.8 with good criteria and cycle III 3.3 with very good criteria. Based on the results of this study, the conclusion is that the Picture and Picture learning model with Picture Media can increase student activity, and students' poetry writing skills. Suggestions for teachers are the Picture and Picture learning model with Picture Media can be used as a reference for the implementation of other learning. It is better for the teacher to carry out self-reflection about the weaknesses in the learning carried out. By using an innovative learning approach, it can increase student activity.